Contributing to the OER movement: A practical experience: The case of the Informatics School, UNA - Rivera, Sonia Mora; Chotto, Mayela Coto (2017 XLIII Latin American Computer Conference (CLEI), 2017)
Open educational resources (OER) propose a culture of sharing to make knowledge a good for humanity. The educational field recognizes the potential of OER to expand access to education and the Information and Communication Technologies (ICT) provide the context for sharing, using and reusing this knowledge. In addition, the OER movement offers scholars the opportunity to rethink their educational practice. Although the literature has shown that academics in general have the practice of sharing their educational resources with close colleagues, it is also true that open and large-scale exchange through appropriate licensing and institutional repositories is an emergent move in many universities. This paper presents an exploratory study to promote, among academics and students, their participation in the OER movement. The experience allowed to generate knowledge on the subject, to develop and validate a set of educational resources to later create in the institutional repository the first OER community.